A Plasmodium falciparum protein tyrosine phosphatase inhibitor identified from the ChEMBL‐NTD database blocks parasite growth. Issue 7 (29th May 2021) - Pandey, Rajan; Gupta, Priya; Mohmmed, Asif; Malhotra, Pawan; Gupta, Dinesh
Abstract : Post‐translational modifications, especially reversible phosphorylation, are among the most common mechanisms that regulate protein function and biological processes in Plasmodium species. Of the Plasmodium phosphatases, phosphatase of regenerating liver ( Pf PRL) is secreted and is an essential phosphatase. Here, we expressed Pf PRL in a heterologous expression system, and then purified and characterized its phosphatase activity. We found that Novartis_003209, a previously identified inhibitor, inhibited the Pf PRL phosphatase activity of recombinant Pf PRL and blocked in vitro parasite growth in a dose‐dependent manner. Further, in silico docking analysis of Novartis_003209 with all four P. falciparum tyrosine phosphatases (PTP) demonstrated that Novartis_003209 is a Plasmodium PTP inhibitor. Overall, our results identify a scaffold as a potential starting point to design a PTP‐specific inhibitor. Abstract : Plasmodium PRL is a secreted protein tyrosine phosphatase and is essential for parasite survival. Our study shows that Novartis_003209 inhibits recombinant Pf PRL phosphatase activity and in vitro parasite growth in a dose‐dependent manner. Further, in silico docking studies with four P. falciparum tyrosine phosphatases suggest that the identified molecule could be a general plasmodium tyrosine phosphatase inhibitor.